The status of pharmacometrics in pregnancy: highlights from the 3(rd) American conference on pharmacometrics - van Hasselt, J G Coen; Andrew, Marilee A; Hebert, Mary F; Tarning, Joel; Vicini, Paolo; Mattison, Donald R (British journal of clinical pharmacology, 2012)
Physiological changes during pregnancy may alter drug pharmacokinetics. Therefore, mechanistic understanding of these changes and, ultimately, clinical studies in pregnant women are necessary to determine if and how dosing regimens should be adjusted. Because of the typically limited number of patients who can be recruited in this patient group, efficient design and analysis of these studies is of special relevance. This paper is a summary of a conference session organized at the American Conference of Pharmacometrics in April 2011, around the topic of applying pharmacometric methodology to this important problem. The discussion included both design and analysis of clinical studies during pregnancy and in silico predictions. An overview of different pharmacometric methods relevant to this subject was given. The impact of pharmacometrics was illustrated using a range of case examples of studies around pregnancy.